Implantação do acolhimento em uma unidade de saúde da família de um município de grande porte do Nordeste brasileiro - Melo, Milena Vieira da Silva (2019)
In Brazil, many challenges stand in the way of implementing the principle of integrality health care, such as the expansion of quality access to services and the lack of preparation of professionals in dealing with the subjective dimension in health care practices. In order to improve the quality of services provided to the population, the Health Ministry created the National Policy for Humanization of Care and Management in the Unified Health System (Sistema Único de Saúde) – HumanizaSUS. One of the guidelines of this policy is the reception, with the proposal to optimize the gateway to service, including the Family Health Unit (FHU), facilitating access and guiding the flow of the user. This study aimed to implement reception as a care management strategy in a FHU of a large city in northeastern Brazil. It was an intervention project with an action research approach. Prior to the implementation of the reception, there was centralization in the doctor and the flow of care was rigid, restricting the population‟s access to service. Complaints and persistent dissatisfaction motivated the team to implement reception in the FHU. Following the change, the new work process made functions more flexible, decentralizing the responsibility of care to the rest of the team and eliminating the daily spontaneous demand queues at the unit‟s door. To assess the implementation of reception, a descriptive and cross-sectional study was conducted by applying a quantitative questionnaire with 210 users and conducting a semi-structured interview with 10 professionals from the FHU. User data was analyzed using descriptive and inferential statistics using Pearson‟s chi-square test with a significance level of 5%. Content analysis with thematic approach was used in the professional‟s speeches. The users evaluated that there was an improvement with the implementation of reception (92.4%, n=194), reflected in the conduct of professionals during the reception (58.6%, n=123), and this positive assessment was significantly related to satisfaction with the information offered by the professionals during the service (p≤0,05). A shorter waiting time for appointment scheduling was also significantly associated with a good user evaluation on the implementation of reception (p≤0,05). Professionals‟ perceptions were also positive and the categories obtained were related to: facilitation of access to the FHU, resoluteness of care, optimization of the work process and humanization as a way to understand the user without restrictions, respecting their differences. The implementation of reception at the FHU provided significant and sustainable changes, affirming the need for integration between care and work process management in the production of health care, with the formation of space for workers to reflect on their practice, in addition to investment in the humanization of services, especially in Primary Care.